(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
In the article, preliminary Ecological Network scheme for the Pivnichne Prychornomoria (Northern Black Sea Coastal Plain) as Key Nature Areas and Ecological Corridors of international and state levels is offered. 15 Key Nature Areas are selected on the base of existing or perspective Biospheric and Natural Reserves, National Natural and Regional Landscape Parks, or their congestions. The majority from 24 Ecological Corridors are situated within valley landscape type. Behind them, necessity of development of watershed Ecological Corridors is proved.